2014
DOI: 10.1002/jcb.24688
|View full text |Cite
|
Sign up to set email alerts
|

Nanotopography Drives Stem Cell Fate Toward Osteoblast Differentiation Through α1β1 Integrin Signaling Pathway

Abstract: The aim of our study was to investigate the osteoinductive potential of a titanium (Ti) surface with nanotopography, using mesenchymal stem cells (MSCs) and the mechanism involved in this phenomenon. Polished Ti discs were chemically treated with H2 SO4 /H2 O2 to yield nanotopography and rat MSCs were cultured under osteogenic and non-osteogenic conditions on both nanotopography and untreated polished (control) Ti surfaces. The nanotopography increased cell proliferation and alkaline phosphatase (Alp) activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0
14

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 31 publications
10
74
0
14
Order By: Relevance
“…Several Ti surface modifications have been proposed in order to improve the process of implant osseointegration 1 , 2 , 6 , 14 , 15 , 17 , 20 . As plasma-nitrided Ti surfaces favor osteoblast differentiation, here, we have investigated bone tissue response to these surfaces and compared with machined ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Ti surface modifications have been proposed in order to improve the process of implant osseointegration 1 , 2 , 6 , 14 , 15 , 17 , 20 . As plasma-nitrided Ti surfaces favor osteoblast differentiation, here, we have investigated bone tissue response to these surfaces and compared with machined ones.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that Ti with nanotopography favors osteoblast differentiation in several culture models 14 , 17 , 20 . Also, biological coatings such as bone apatite and type I collagen enhance bone formation in contact with Ti implants 6 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, α1 and β1 integrin gene expression was higher in cells grown on nanotopography under nonosteogenic conditions compared with those on a control Ti surface. The higher osteogenic gene expression induced by Ti with nanotopography was reduced by obtustatin, a α1β1 integrin inhibitor …”
Section: Effect Of Nanotopography On Osteogenic Differentiationmentioning
confidence: 99%
“…Osteogenic cells and proteins of the extracellular matrix can interact with nano-sized surface features, triggering biological pathways for faster bone healing [2][3][4][5]. Intriguingly, most of the commercially available implants possess randomized nano-sized surface features, normally formed spontaneously by the oxidation of titanium in air [6].…”
Section: Introductionmentioning
confidence: 99%